1987
DOI: 10.1080/01483918708066806
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Eluents in Supercritical Fluid Chromatography

Abstract: The chromatographic behavior of a number of low boiling eluents has been compared in supercritical fluid chromatography ( S F C ) with packed columns. Unmodified silica gel has been used as the stationary phase and a test mixture of polycyclic aromatic hydrocarbons ( P A H I S ) as the substrate. Carbon dioxide, nitrous oxide, trifluoromethane, chlorotrifluoromethane, n-pentane, n-butane, 1-butane, propane, ethane, dicthylether, and dimcthylethtr have beon investigated as mobile phases. LEYENDECKER ET ALOf the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…This behavior is typical of near-critical mobile phases. 11,12 When carbon dioxide was replaced by HFC-134a, comparable behavior was observed (Fig. 2).…”
Section: Retentionsupporting
confidence: 83%
“…This behavior is typical of near-critical mobile phases. 11,12 When carbon dioxide was replaced by HFC-134a, comparable behavior was observed (Fig. 2).…”
Section: Retentionsupporting
confidence: 83%
“…On comparing retention between chemically similar mobile phases at the same temperature and pressure in SFC it is observed that the transport ability decreases with decreasing boiling temperature (and critical temperature) of the eluent. This has been reported for a comparison of alkanes from pentane to propane [2,3], and the still higher retention obtained with an ethane mobile phase [4] corresponds to this trend. Similarly, retention was higher with dimethyl ether than with diethyl ether [l].…”
Section: Methodssupporting
confidence: 78%
“…This effect is well known and can mainly be attributed to the increased solvating ability of the mobile phase at higher density, although other factors are important. [16][17][18][19] This effect is not specific to the chiral recognition process since a similar effect is observed when the same analytes are chromatographed on a cyano bonded phase.…”
Section: 15supporting
confidence: 54%